METHODOLOGICAL IMPROVEMENT OF TEACHING MEDICAL PHYSICS BASED ON THE INTEGRATION OF STEAM AND EXPERIMENTAL APPROACHES - Khomidjonov Jaxongir Isroiljonovich (Bright Mind Publishing, 2025)
The modern educational process is not aimed at the student's memorization of ready-made knowledge, but at the formation of independent thinking, analysis and creation of new ideas. Especially in the subject of medical physics, it is important to develop students' ability to understand scientific phenomena through experiments and observations. Therefore, demonstration experiments and the STEAM approach play a key role in the effective organization of the educational process. The article discusses the ways, stages and evaluation criteria for conducting demonstration experiments in medical physics lessons and methodologically improving the educational process based on STEAM integration.
Keywords: Medical physics, demonstration experiment, STEAM approach, computed tomography, X-ray, detector, experimental methodology, integration.